A Research Study on the Prevalence of Diabetic Retinopathy in Newly Diagnosed Type 2 Diabetes Mellitus Patients Presenting to a Tertiary Care Hospital - Muhammad Aqeel, Muhammad Usman, Liaquat Ali, Hina Azeez, Nasir Ashraf, Muhammad Jahangir Adil (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To quantify the prevalence of type II diabetes patients with recently diagnosed diabetic retinopathy. Materials & Methods: The design of this study was cross sectional study design and this study was conducted in Pakistan institute of medical science. There were 113 cases in total of the freshly diagnosed diabetes mellitus type II patients, of age from 30 to 60 years. The patients who had hypertension, diabetes type I, or a history of retinal surgery were not allowed to participate. Following a fundoscopic examination of all patients, the absence or presence of the retinopathy and grades of the retinopathy were noted. Results: The patients’ average ages were 45.46±7.40 years. The male to female ratio of these 113 patients was 1.6:1, with 69 (61.06 percent) men and 44 (38.94 percent) women. 18 individuals (15.93%) had retinopathy, according to the results, while 95 patients (84.07%) had none. Practical Implication: This study would assist us in screening these high-risk patients. Additionally, a comprehensive ophthalmic examination at diagnosis time of the diabetes and the periodic screening for detection of retinopathy early so that the early therapeutic measures could be taken for prevention of their further complications could be arranged for all freshly diagnosed diabetic type-2 patients. These programs could be organized at regional and national levels. Conclusion: This study’s findings, which include the relatively high prevalence of the diabetic retinopathy in the freshly diagnosed Diabetes mellitus type II patients at 15.93 percent, which highlights the need for each patient to undergo a thorough Ophthalmic examination at the time of being labelled as diabetic. Keywords: Diabetes, freshly diagnosed, Diabetic Retinopathy Prevalence, retinopathy, Diabetes Mellitus Type II.